ESTABILISHING HARMONY BETWEEN RELIGIONS BY THE RELIGIOUS HARMONY FORUM IN PAPUA THE LAND OF PEACE MAQASID SYARI’AH PERSPECTIVE - Amirullah, Amirullah; Salenda, Kasjim; Said, Nurman; Haddade, Abdul Wahid (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This writing tells about the endeavor of FKUB, or the Religious Harmony Forum in the city of Jayapura in estabilishing harmony between religions in Jayapura-Papua The Land of Peace in Maqasid Syari’ah perpective. This is an analytical descriptive research aimed to explain explicitly about the existence of FKUB in estabilishing the religious harmony according to the Maqasid Syari’ah point of view. The result shows that the effort of FKUB in Jayapura led to five points of priority measurement applied to maintain the harmony between religions. Those are as follows: a) preserving religions in Dharuriyyat (basic needs) level in the effort of estabilishing harmony of religious groups through dialogue in one’s group to be persuasive; b) preserving spirit (Hifz) is a basic need (dharuriyyat). Otherwise, people would fail to present seminars, dialogue, and contain people aspirations; c) preserving intelligence (Hifz al-‘Aql) is obviously fundamental to create harmony; d) preserving successors in daruriyyat level. It is also fundamental for better upcominng future; e) educating relgious figure how to maximally maintin prosperity.